Child, teacher and preschool characteristics and child-teacher relationships in Greek preschools - Šumatić, M; Malmberg, L-E; Gregoriadis, A; Grammatikopoulos, V; Zachopoulou, E (Elsevier, 2023)
Three dimensions of child–teacher relationships (derived from the Student-Teacher Relationship Scale) closeness, conflict and dependency have been conceptualized and investigated. In individualistic cultures a close relationship has been associated with children's academic performance and behavioural adjustment, conflictual relationships have been associated with maladjustment and externalising behaviours, and the dependency dimension has been negatively associated with closeness. We expand previous studies by first investigating the factor structure of the STRs amongst 2,130 preschool children and their 267 teachers in a collectivistic culture, Greece. Second, we investigated effects of child (gender, age, country of origin and special educational needs), teacher (teacher gender, age and affective well-being), and preschool characteristics (school-type, number of children, observed quality using the Early Childhood Environment Rating Scale-Revised (ECERS-R), on STRS.